Modeling of Cathodic Protection for pipe lines - Alhabobi, Naseer A.; Albayati, Anas Th. (Journal of Petroleum Research and Studies, 2016)
Corrosion is an international problem with more structures and materials buried in the soil. The most common and applicable technique to overcome this problem is cathodic protection. In this work a Carbone steel pipe of length 100 cm is buried in a wooden box submerged by soil and Impressed Current Cathodic Protection system was applied using power supply and close circuit, several important factors has been studied, like Anode position (distance and depth), soil resistivity (wet and dry), condition the pipe (coated and un-coated), distribution of potential and currents along the pipe (cathode), the amount of current required to achieve cathodic protection. A mathematical model was developed to simulate the ranges of parameters and factors affecting Impressed Current Cathodic Protection (ICCP). Regression of this model to data and results yielded parameter values vary depending on the effect of the same factor.